2009
DOI: 10.1089/omi.2009.0008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Analysis Integrated with Microarray Data Reveals That Extracellular Matrix Proteins, Catenins, and P53 Binding Protein 1 Are Important for Chemotherapy Response in Ovarian Cancers

Abstract: Chemotherapy with carboplatin and paclitaxel is the standard treatment for ovarian cancer patients. Although most patients initially respond to this treatment, few are cured. Resistance to chemotherapy is the major cause of treatment failure. We applied a quantitative proteomic approach based on ICAT/MS/MS technology to analyze tissues harvested at primary debulking surgery before the initiation of combination chemotherapy in order to identify potential naive or intrinsic chemotherapy response proteins in ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 42 publications
3
58
0
Order By: Relevance
“…However, a consensus on the effects of 53BP1 on cellular responses to chemotherapeutic agents has yet to be reached, with multiple studies having demonstrated increased or decreased drug sensitivity with 53BP1 overexpression (11,32,33). These conflicting reports suggest that the association between 53BP1 and chemosensitivity may be more complex than previously assumed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a consensus on the effects of 53BP1 on cellular responses to chemotherapeutic agents has yet to be reached, with multiple studies having demonstrated increased or decreased drug sensitivity with 53BP1 overexpression (11,32,33). These conflicting reports suggest that the association between 53BP1 and chemosensitivity may be more complex than previously assumed.…”
Section: Discussionmentioning
confidence: 99%
“…paclitaxel-resistant and sensitive-cell models 26,27 or chemoresistant and chemosensitive tissues from ovarian cancer patients 28 by different proteomic techniques, such as 2-dimensional electrophoresis (2DE) or difference gel electrophoresis (DIGE) coupled with mass spectrometry, and isotope-coded affinity tags (ICAT) labeling combined with LC-MS proteomic analyses. In the present study, we identified 356 proteins differentially expressed at a 1.5-fold or higher intensity between a paclitaxel-resistant www.tandfonline.comSKOV3-TR30 and a paclitaxel-sensitive SKOV3 cell line using LC-MS/MS label-free quantitative proteomic analyses with spectral counting strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding ECM components are upregulated in tumors that are resistant to anticancer treatments (Pan et al, 2009;Sherman-Baust et al, 2003), and tumor cell adhesion to the ECM increases resistance to anticancer agents (Streuli and Gilmore, 1999). Moreover, remodeling of the ECM in response to irradiation is suggested to contribute to genomic instability and carcinogenesis induced by ionizing radiation (Barcellos-Hoff, 1998).…”
Section: Discussionmentioning
confidence: 99%